The Fauna of Springtails (Collembola) from the Forest Ecosystems of South-East Ukraine - Bondarenko-Borisova, I.V.; Sandul, N.G. (Вестник зоологии, 2002)
The fauna of springtails (Collembola) was investigated for seven years in natural forest ecosystems of the Donetsk highland, namely in gully forests, flood-land forests and highland woods. The list of Collembola of forest habitats of the eastern Ukraine has been compiled basing on the original and literature data. It includes 115 species belonging to 52 genera and 16 families. The core of the fauna of Collembola in investigated forests is formed by such families as Entomobryidae, Onychiuridae and Isotomidae. Eight zoogeographical complexes of species were defined by the authors. The European, the Holarctic and the cosmopolitan complexes predominate in the number of species. Species richness, representation of ecological groups, life forms and Collembola hygromorphs differ in the three types of forests investigated. Most of the biotopes are characterized by the predominance of forest species, the considerable representation of eurybionts as well as meadow and steppe forms of species, the predominance of upper-litter biomorphs and a wide spectrum of hygromorphs. The ecological-faunistic peculiarities of springtails ecosystems reflect the specifics of forest microclimate in steppe and can be used for zoodiagnostics of natural and artifical forests. В течение 7 лет изучали фауну ногохвосток в естест-венных лесах на Донецком кряже, а именно: в байрачных, пойменных и нагорных лесах. На основании авторских и литературных сведений составлен список коллембол лесных биотопов Левобержной Украины, включающий 115 видов из 52 родов и 16 семейств. Ос-нову фауны исследованных лесов формируют семейства Entomobryidae, Onychiuridae и Isotomidae. Авторами выделено 8 зоогеографических видовых комплексов, среди кото-рых преобладают (по числу видов) европейский, голарктический и космополитный. В трех исследованных вариантах лесов видовое богатство, соотношение экологических групп, жизненных форм и гигроморф коллембол отличаются. Большинству биотопов при-суще долевое преобладание лесных видов и верхнеподстилочных биоморф, значительная представленность эврибионтных, луговых и степных форм, разнообразие спектра гигро-морф. Эколого-фаунистические особенности сообществ ногохвосток отражают специфику лесного микроклимата и могут использоваться для зоодиагностики естественных и искусственных лесонасаждений в степной зоне.